Studi Analisis Gangguan Hubung Singkat Jaringan Transmisi GI Jajar-Gondangrejo-Palur Menggunakan ETAP 12.6 - Pratama, Yaniar Nur Ihsan; , Umar, S.T., M.T (2017)
Electricity has become a necessity that can not be separated to each individual. Almost all the equipment using electrical energy. Demand for electricity increases with the increase of population. In Indonesia are PT PLN (Persero) which provides electrical services include power generation, transmission, and distribution. In the case of the transmission itself is not separated from the short circuit fault arising from various factors. Short circuit consists of a 3-phase short circuit, phase to phase short circuit, single phase to ground short circuit, and a double phase to ground short circuit. Short circuit analysis aims to determine the current values as a result of a short circuit. Short circuit analysis carried out on transmission line of Power station Jajar-Gondangrejo-Palur using ETAP 12.6. The method used is starting from gathering the data in Power station Jajar-Gondangrejo-Palur, create a single line diagram in ETAP 12.6, checking the single line with a load flow simulation, doing short circuit analysis simulation, perform manual calculations, comparison, and conclusions. The conclusion of the short circuit fault analysis is the current value is affected by impedance and conductor length, the greater the distance the greater the conductor impedance value then the value of short-circuit fault current will be of little value and vice versa. To the nearest bus is GI Gondangrejo bus, has a 3 phase current amounted to 1,728 kA, 1,497 kA for phase to phase fault, 2,062 kA for phase to ground fault, 1,993 kA for double phase to the ground fault. Short circuit fault current can be used to determine the capacity of the security protection.